Unreliability of Serum‐ or Plasma‐based Assays of D‐dimer or Fibrin (Fibrinogen) Degradation Product for Diagnosing Periprosthetic Joint Infection: A Prospective Parallel Study - Hong Xu; Jing Zhou; Qiang Huang; Zeyu Huang; Jinwei Xie; Zongke Zhou (Orthopaedic Surgery, 2024)
Objective The ability of D‐dimer to diagnose periprosthetic joint infection (PJI) before revision hip or knee arthroplasty is still controversial, and the differences in diagnostic ability between serum‐ or plasma‐based assays of D‐dimer and fibrin (fibrinogen) degradation product (FDP) are uncertain. The prospective parallel study was performed to determine the ability of D‐dimer to diagnose PJI before revision hip or knee arthroplasty, and the differences in diagnostic ability between serum‐ or plasma‐based assays of D‐dimer and FDP. Methods Patients undergoing knee or hip arthroplasty at our institution were prospectively enrolled into the following groups: those without inflammatory diseases who were undergoing primary arthroplasty (“Prim” group), those with inflammatory arthritis who were undergoing primary arthroplasty (“Prim/Inflam”), those undergoing revision arthroplasty because of aseptic failure (“Rev/Asept”), or those undergoing revision arthroplasty because of PJI (“Rev/PJI”). The ability of preoperative levels of D‐dimer or FDP in serum or plasma to diagnose PJI in each group was assessed using areas under receiver operating characteristic curves (AUCs) and other diagnostic performance indicators. The diagnostic performance of these assays was compared with that of C‐reactive protein (CRP) and erythrocyte sedimentation rate (ESR). Results In the final analysis, Prim included 42 patients; Prim/Inflam, 40; Rev./Asept, 62; and Rev./PJI, 47. D‐dimer assays led to AUCs of 0.635 in serum and 0.573 in plasma, compared to 0.593 and 0.607 for FDP. Even in combination with CRP or ESR, these assays failed to perform as well as the combination of CRP and ESR for diagnosing PJI. Conclusion Levels of D‐dimer or FDP in serum or plasma, whether used alone or together with CRP or ESR, are unreliable for diagnosing PJI before revision arthroplasty.